Die ATKV as kultuurorganisasie binne ‘n veranderende Suider-Afrikaanse samelewing - Pieter Möller (Contree)
The Afrikaanse Taal en Kultuur Vereeniging (ATKV) is an organisation aimed at developing Afrikaner culture and language by hosting several projects. The role of the ATKV changed considerably after the transformation of South Africa to a multi-racial democracy in 1994. The changing context will be approached from historical perspective, and specific attention will be paid to the role that the ATKV currently plays in the new South African society. This article considers the organisation’s change of focus, management and attitude within this new context. The main question that this article wants to debate is whether this organisation indeed succeeds in enhancing, deepening and expanding Afrikaner culture and whether it is a modern and dynamic organisation. Some of the projects hosted by the ATKV will be evaluated to indicate in what measure this organisation reaches out to other cultures and what influence it has on the broader South African society. To rethink identity and memory within the new South African society, membership of the ATKV as well as its implementation within a system of cultural branches operating countrywide, will be evaluated critically. The article will show that the ATKV’s activities are aimed at achieving its goals with drive and creativity. The organisation achieves this through its many intercultural projects focused on enhancing relationships between the different cultural groups in South Africa. Ultimately, it is argued that the ATKV plays a critical and crucial role that benefits, or will benefit the broader South African society in the 21st century.